Facing The Truth: An Appraisal Of The Potential Contributions, Paradoxes And Challenges Of Implementing The United Nations Conventions On Contracts For The International Sale Of Goods (Cisg) In Nigeria. - Ajibo, Kenneth I (Journal of Sustainable Development Law and Policy, 2025)
Nigeria is currently not a contracting party to the United Nation Convention on Contracts for the International Sale of Goods (CISG), which governs transactions and sales of goods globally. Sadly enough, the current legal framework regulating the sale of goods in Nigeria remains the 18th century Sale of Goods Act 1893 which is arguably obsolete and out of touch with modern day business reality. This paper argues that despite the potential practical challenges in implementing the CISG, Nigeria has a lot to gain economically by becoming a contracting party to CISG; particularly as the nation inches toward the target of becoming one of the world’s twentieth largest economies by 2020.